Investigation on mechanical properties of lightweight aggregate concrete containing coal ASH as partial sand replacement - Aisyah Aqilah, Akmal (2019)
The increasing demand for electricity consumption and the production from oil palm industry have contributed to increasing the production of waste materials. The high demand for coal by power plants, increase the production of coal ash. Malaysia as the world largest exporter of oil palm shell also have produced a vast amount of solid waste and can be a cause of the environmental problem. Instead of expanding the available landfill, the utilization of the waste materials would be very useful since it required a lesser cost. Rather than that, utilization of these waste materials in construction industry increase chances in solving environment problem. In this study, investigations have been carried out in order to figure out the compressive strength, flexural strength, and modulus of elasticity of oil palm shell lightweight concrete containing coal bottom ash as partial sand replacement. Saturated surface dry oil palm shell was used as coarse aggregate in the concrete. Coal bottom ash was used as partial sand replacement for 0%,10%, 20%, and 30%. All specimens were subjected to air curing method. The compressive strength test and flexural strength test were conducted at 7-day, 28-day, and 60-day. Meanwhile, modulus of elasticity tests was conducted at 28-day. Based on the three tests conducted, it can be concluded that the strength of the concrete reaches the maximum with 10% partial replacement of sand by coal bottom ash. The strength of the concrete started to decrease with increasing percentage replacement of coal bottom ash. As a conclusion, the optimum replacement of coal bottom ash can be used to produce higher concrete strength.